Analysis of the fencing lunge based on the response to a visual stimulus and a tactile stimulus - Borysiuk, Z.; Markowska, N.; Niedzielski, M. (Journal of Combat Sports and Martial Arts, 2014)
The aim of the study was to determine the dynamic structure of the fencing lunge through determining the sequence of arousal in the following muscles: the rectus femoris and the biceps femoris of the front leg, the gastrocnemius muscle (medial and lateral head) in the back leg, biceps brachii, triceps brachii and the brachioradial muscle in the armed upper limb. Moreover, the experiment assumed determining the mean bioelectrical muscle tension. Material and methods. The sample comprised six right-handed competitors of the hitherto existing provincial fencing team from Silesia. The competitors made six attempts of a simple lunge: three for one trainer`s step forward (without touché) and three for losing contact on the blade. The study used a 16-channel system Noraxon EMG, recording bioelectric activity of muscles (connection according to SENIAM recommendation). The EMG system was synchronised with one camcorder (Point Grey Ga zelle), an additional software ProAnalysis (CRI Jolanta Polska) and the EMG system (MyoResearch XP MT-400). Results. During the simple lunge for the trainer`s step forward, namely during the response to a visual stimulus, the triceps brachii muscle of the armed limb was first stimulated. Immediately after this stimulation, the lateral head of the gastrocnemius muscle was tensioned. During the simple lunge for losing contact on the blade (withdrawing the trainer`s blade from the competitor`s blade), namely during the response to tactile stimulation, first the gastrocnemius muscles of the back leg were simultaneously activated. The results reflecting the mean muscle tension indicate elevated values during the simple lunge for losing contact on the blade. Conclusions. 1. In response to the visual stimulus, the triceps brachii of the armed upper limb is activated first, which is confirmed by the first point of the classic scheme of the sequence of a simple lunge. 2. In response to the tactile stimulus, the sequence of stimulation of the triceps brachii musle with the gastrocnemius muscle, whose lateral head together with its medial head are activated first during a simple lunge, is altered. 3. The results reflecting the mean values of muscle tension indicate that the activity of visual stimuli evokes greater accumulation of bioelectrical potentials than tactile stimulation which shows that waiting for a visual stimulus and observation of visual stimuli result in reduction of muscle tension.